Effects of Persian leek (Allium ampeloprasum) on hepatic lipids and the expression of proinflammatory gene in hamsters fed a high-fat/ high-cholesterol diet - Vahideh Fatoorechi; Marjan Rismanchi; Javad Nasrollahzadeh (Mashhad University of Medical Sciences, 2016)
Objective: Persian leek is one of the most widely used herbal foods among Iranians. In this study, effects of oral administration of Persian leek on plasma and liver lipids were examined in hamster. Materials and Methods: Male Syrian hamsters were randomly divided into three groups: control (standard diet), high fat control (high-fat/high-cholesterol diet), Persian leek (high-fat/high-cholesterol diet + 1% per weight of diet from dried powdered Persian leek) for 14 weeks. Results: High fat diet increased plasma and liver lipids as compared to standard diet. Adding Persian leek to the high-fat/high-cholesterol diet resulted in no significant changes in the concentration of the plasma lipids or liver cholesterol. However, liver triglycerides (TG), plasma Alanine aminotransferase and gene expression of tumor necrosis factor- α were decreased in hamsters fed high-fat diet containing Persian leek as compared to high-fat diet only. Conclusion: Persian leek might be considered as a herbal food that can reduce liver TG accumulation induced by high fat diets.